STAGE DEVELOPMENT INITIAL IMAGERY AND PROCESS MODERNIZATION IMAGERY - Turgunbayeva Tazhigul (Western European Studies, 2024)
The article examines the process of implementing the development strategy of New Uzbekistan; in the conditions of modernization of education, the ideology of primary education is changing significantly. Primary school today is called upon to fulfill the most important tasks: to create conditions for the initial formation of the personality of a young student, to give children the opportunity to “start on an equal footing” and prepare them for the next stage. level.
Keywords: education; upbringing; primary education; system